Aqueous synthesis of three-dimensional fluorescent silicon-based nanoscale networks featuring unusual anti-photobleaching properties. Issue 5 (18th December 2018) - Zhong, Yiling; Chu, Binbin; Bo, Xin; He, Yao; Zhao, Chuan
Abstract : Three-dimensional fluorescent silicon-based nanoscale networks (SiNNs) possess unusual anti-photobleaching properties, owing to a unique electronic structure system. Abstract : We herein present the first example of three-dimensional (3D) fluorescent silicon-based nanoscale networks (SiNNs), which feature unusual anti-photobleaching properties, owing to a unique electronic structure system. This type of fluorescent and biocompatible SiNN, prepared through self-assembly synthesis under microwave irradiation, holds high promise for various optical and electronic applications.